Rotonda Mihail Sebastian (MLR, 1975) 30 de ani de la moarte - Lucian Chișu (Revista de Istorie și Teorie Literară)
During the communist period, literary history recorded its main events through the writing of experts in the field. The resulting image is undoubtedly truthful and it renders in its entirety the evolving ”scale of values“ of Romanian literature, including the literature of the last half a century, a period supposed to have been affected by the distortions operated by the political climate. The maintenance of the necessary balance is an undeniable fact, despite some interventions” of the last two decades, which aimed to be the seismograph of the intrusions of social command; in other words, of the communist propaganda in matters of literary art and its main themes. The only element remaining under question refers to a certain attitude, to the ”official character of the enterprise of those who approached literary history, which disregarded the immanence of the ideological factor (”the Party is everything“), implying, beyond the configuration of artistic hierarchies, the non-interference in state politics, considered as extraneous to literature itself. We had therefore a panoramic image of our literary landscape which lacked, due to a subtle ablution of memory, the ideological component, perfectly substituted by aesthetic arguments of expressivity or the art of the word. Contemporary Romanian history was projected by the same literary historians on an apparently atemporal axis, albeit Romanian. In this manner, the literary histories and works of criticism dedicated to the prominent figures of Romanian writing were confined solely to the aesthetic realm, away from the revolutionary enthusiasm which haunted society like an epidemic and found fervent adepts in other sectors. In conclusion, our literary histories were sincere, but somehow incomplete, or rather, between the lines of their substance; the careful reader could easily discover the feared secret of Polichinelle: the things known only too well to everyone were no longer mentioned. However, beyond the written literary history, which it came to complete, there also circulated in the literary forums an unwritten, oral literary history, in which the passages we called Polichinelle’s secret occupied a privileged position. The false values promoted according to ”Party and state lines“, consistently omitted from the above mentioned literary histories, were subject to severe criticism and bitterly ironic admonitions, while the personalities who could hardly be mentioned — not in writing, but in a whisper — were restored to their rights. Nevertheless, this unwritten literary history righted official wrongs, that is, those ignored in the literary histories, and it did so in an absolutely transient manner, as the truths exposed in such contexts did not last longer than the oxygen expired from the speaker’s lungs. We all know about the existence of those unwritten (oral) literary histories and agree that, on the whole, they. completed the picture by reintegrating in the natural corpus the artists regarded as undesirable by the Party. Besides the situation depicted above, we note the existence of yet another component, brought to the attention of the reading public and of those acquainted with literary history: ”Rotonda“ series, initiated by the Publishing House of the Romanian Literature Museum. Literary confessions had proved long before their complementarity and particular utility. ”Rotonde 13″, title under which the events organized by the National Museum of Romanian Literature became known, continued to take place, in their established good tradition, on the 13th of each month, a date observed strictly, save a few, well-justified exceptions, when the date was moved a little before or after what we believe to be the lucky day of this unique phenomenon in Romanian culture. The text of Mihail Sebastian’s Rotonda expose our presentation.